ADVANCING FUTURISTIC DIGITAL BANKING: STRATEGIC ENHANCEMENT AND A ROADMAP FOR EXCELLENCE - Pratama, Kristianus Jimy (Journal of Central Banking Law and Institutions, 2025)
This research aims to rectify misconceptions surrounding banking digitalisation and conduct an in-depth analysis of Bank Indonesia and the Financial Services Authority’s (OJK) policies concerning developing and enhancing the banking sector’s digitalisation. Additionally, this study is designed to formulate a strategic roadmap for developing banking sector digitalisation, accompanied by risk mitigation processes. The fundamental misconception identified herein pertains to the limited understanding of banking digitalisation as merely transitioning from conventional to digital services. This narrow perspective, still embraced by regulatory authorities, adversely impacts national banking industry stakeholders. Employing a normative legal research methodology through an extensive literature review, our findings reveal a prevailing tendency towards structural collaboration in policy formulation rather than embracing synergistic approaches. This research underscores the urgency of formulating visionary and flexible policies in banking digitalisation. Based on the findings, this study seeks to build the framework for policy formulation by regulation authorities in conducting further studies regarding the direction of policies for developing and strengthening banking sector digitalisation.